2020
DOI: 10.1038/s41386-020-0743-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulating microglia activation prevents maternal immune activation induced schizophrenia-relevant behavior phenotypes via arginase 1 in the dentate gyrus

Abstract: Prenatal infection during pregnancy increases the risk for developing neuropsychiatric disorders such as schizophrenia. This is linked to an inflammatory microglial phenotype in the offspring induced by maternal immune activation (MIA). Microglia are crucial for brain development and maintenance of neuronal niches, however, whether and how their activation is involved in the regulation of neurodevelopment remains unclear. Here, we used a MIA rodent model in which polyinosinic: polycytidylic acid (poly (I:C)) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 87 publications
1
32
0
Order By: Relevance
“…IL4-induced Arg1 + microglia can be thought of a special phenotype of beneficial microglia ( 21 , 30 ). These cells regulate inflammatory processes in the brain and enhance neurite growth, thereby exhibiting neuroprotective effects ( 20 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL4-induced Arg1 + microglia can be thought of a special phenotype of beneficial microglia ( 21 , 30 ). These cells regulate inflammatory processes in the brain and enhance neurite growth, thereby exhibiting neuroprotective effects ( 20 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL4 deficiency weakens the resilience against stress-induced depression, while increasing IL4 levels can alleviate depressive-like behaviors ( 18 , 19 ). Studies have shown that IL4 can reprogram microglia toward an Arg1 + phenotype for maintaining brain homeostasis, neuroprotection, and tissue repair ( 20 , 21 ). However, the effects of IL4-induced Arg1 + microglia on neurogenesis and stress resilience are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…MIA produces an increase in pro-inflammatory cytokines and MMP-9 release in the fetal body, both of which are inducers of microglial activity [ 28 ]. Prenatal infections and MIA are furthermore associated with microglial overactivation in children [ 31 ]. Interestingly, prenatal infections have recently been reported to cause astrocytes to react in a hypersensitive manner to stimuli in the future [ 32 ].…”
Section: Environmental Factors Implicated In Synaptic Pruningmentioning
confidence: 99%
“…Tamoxifen administration was performed as we previously described [ 31 ]. Myh6-CreER mice were crossed with ARG 2 f/f mice to get Myh6-CreER; ARG 2 loxp/loxp (Myh6-ARG 2-/-).…”
Section: Methodsmentioning
confidence: 99%